The Role of Ca2 + in Maturation and Reprogramming of Bovine Oocytes: A System Study of Low-Calcium Model - Meng, Lin; Hu, Hongmei; Liu, Zhiqiang; Zhang, Luyao; Zhuan, Qingrui; Li, Xue; Fu, Xiangwei; Zhu, Shien; Hou, Yunpeng (Frontiers in Cell and Developmental Biology, 2021)
[Ca2+]i is essential for mammalian oocyte maturation and early embryonic development, as those processes are Ca2+-dependent. In the present study we investigated the effect of [Ca2+]i on in vitro maturation and reprogramming of oocytes in a lower calcium model of oocyte at MII stage, which was established by adding cell-permeant Ca2+ chelator BAPTA-AM to the maturation medium. Results showed that the extrusion of the first polar body (PB1) was delayed and oocyte cytoplasmic maturation, including mitochondria and endoplasmic reticulum distribution, was impaired in lower calcium model. The low calcium model oocytes presented a poor developmental phenotype of Somatic Cell Nuclear Transfer (SCNT) embryos at the beginning of activation of zygotic genome. At the same time, oxidative stress and apoptosis were observed in the low calcium model oocytes, subsequently RNA-Seq analysis of the lower calcium model oocytes screened 24 genes responsible for the poor oocyte reprogramming, and 6 genes (ID1, SOX2, DPPA3, ASF1A, MSL3, KDM6B) was identified by Quantitative PCR. Analyzing the expression of these genes is helpful to elucidate the mechanisms of [Ca2+]i regulates oocyte reprogramming. The most significant difference gene in this enriched item was ID1. Our results showed that the low calcium might give rise to oxidative stress and apoptosis, resulting in impaired maturation of bovine oocytes, and possibly affecting subsequent reprogramming ability through the reduction of ID1.